2017
DOI: 10.1016/j.wneu.2017.04.128
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic In Vivo Visualization of Pituitary Adenomas: a Systematic Review of Imaging Modalities

Abstract: Introduction Pituitary adenomas are the most common intrasellar mass. Functional pituitary adenomas (PAs) constitute the majority of pituitary tumors and can produce symptoms related to hormonal overproduction. Timely and accurate detection is therefore of vital importance to prevent potentially irreversible sequelae. Magnetic resonance imaging (MRI) is the gold standard for detecting PAs, but is limited by poor sensitivity for microadenomas and an inability to differentiate scar tissue from tumor residual or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
5
0
1
Order By: Relevance
“…We have identified aqueous metabolites (in the methanol-water layer) and lipid components (in the chloroform layer) by analyzing 1D 1 H and 2D 1 H- 1 H TOCSY NMR spectra in combination with comparison of chemical shifts reported in the literature 3,9–15 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have identified aqueous metabolites (in the methanol-water layer) and lipid components (in the chloroform layer) by analyzing 1D 1 H and 2D 1 H- 1 H TOCSY NMR spectra in combination with comparison of chemical shifts reported in the literature 3,9–15 .…”
Section: Methodsmentioning
confidence: 99%
“…PAs may interfere with normal production of one or more of the pituitary hormones as they grow and compress and/or destroy the normal pituitary gland. The growth of PAs and hypersecretion of hormones can produce a number of clinical symptoms, the consequences of which produce clinical syndromes and therapeutic challenges 3,4 . Although routine diagnostic magnetic resonance imaging (MRI) is used to diagnose most PAs, it may not detect microadenomas unambiguously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional imaging examinations, such as positron emission tomography/ computed tomography (PET/CT) and PET/MRI, could contribute to the evaluation of the tumor location. 18 Ffluorodeoxyglucose (FDG) PET/CT is proposed to be positive in 60-67% of cases in studies involving pituitary adenomas (27,28), which can be meaningful for detecting adenomas, especially when the MRI findings are unclear. Ishizaki et al proposed that PET/CT revealed increased FDG uptake in EPA patients (4).…”
Section: Diagnosis Of Ectopic Tsh-oma In the Sellar Regionmentioning
confidence: 99%
“…Среди возможных точек приложения данных методик следует указать визуализацию невидимых на МРТ-изображениях микроаденом, а также обнаружение остаточных фрагментов опухоли и раннее выявление рецидивов. Ряд работ посвящен изучению радиофармпрепаратов, специфичных для рецепторов соматостатина ( 111 In-пентетреотид для сцинтиграфии [72], 68 Ga-DOTA-TATE для ПЭТ [73]), дофаминовых рецепторов ( 123 I-эпидеприд [74]), а также более распространенных 18 F-фтордезоксиглюкозы и 11 C-метионина [75]. По мнению A. Yao и соавт.…”
Section: Russian Journal Of Neurosurgeryunclassified